The cost and effect of occupational health hazards a case study of proton manufacturing plant Malaysia / Siti Faeruza Hassam - Hassam, Siti Faeruza (2013)
There are many hidden costs which management erroneously believe do not affect their cost calculation and profit performance as a well. It is actually can be broadly classed as insured and uninsured or hidden costs which arise after a safety and health issues takes place. This research is conducted to study the uninsured cost or hidden costs effect of occupational health hazards mainly focus for Perusahaan Otomobil Nasional Sdn Bhd PROTON manufacturing plant Malaysia. It is aims to determine the relationship between occupational health hazards in workplace with its cost implication (uninsured cost) by focusing on ergonomic, physical, chemical and biological hazards factor. It is measured in terms of working environment conditions, human error and management failure. Meanwhile, identified costs associated which are loss times, training cost, employees’ morale and productivity cost are measured to determine the cost related due to workplace safety and health issues. Besides, it is intended to establish the uninsured cost estimation equation model that can be used in minimizing the cost implication due to major health hazards factor intervention in workplace. With several Occupational Safety and Health (OSH) programs implemented this research also identified the relationship between those OSH practices with the safety and health issues in the company. A descriptive study is undertaken in order to ascertain and able to describe the major factors of occupational health hazards with the cost implication interest in a workplace situation. A comprehensive questionnaire was design base on all determined issues and distributed to the employees’ representative through self-administered method. To strengthen the findings gathered, semi-structured interview session was conducted with the Safety Manager of PROTON Malaysia in helping of elaboration and verification for further detail. It was revealed that, phvsical hazard factor is most outstanding occupational health hazards followed by chemical hazard factor. Hence to end of this study, final estimated equation for minimize cost calculation due to physical and chemical hazard factors have been suggested ( y = 3.745 + 0.409xi + 0.344x2). There are also some beneficial recommendations made in minimizing the cost insured resulted from the safety and health issues in workplace. Other than determining the major health hazards and its cost implication to the company, this study is also an attempt to motivate employers and employees to improve their health and safety performance as well as to guide them in measuring the costs implication due to health and safety failure.